Catalytic hydrogenation of carbon dioxide by platinum doped nickel oxide catalyst - Alina Rahayu, Mohamed; Zarina, Zakaria; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr. (IDOSI Publications, 2010)
Link to publisher's homepage at http://www.idosi.org/index.htm